Pengaruh Employer Branding, Corporate Reputation Dan Organizational Attractiveness Terhadap Intention to Apply (Studi Kasus Karyawan Swasta Gen Z di Kota Surakarta) - Silvi Kurniawati; Nike Larasati (Teewan Journal Solutions, 2026)
This study aims to analyze the significant influence of employer branding, corporate reputation, and organizational attractiveness on the intention to apply for private sector employees. This study is a survey of Gen Z employees in Surakarta City. The data used is quantitative, with primary data sources. The population in this study was Gen Z private sector employees in Surakarta City. The sample size was 100. Data collection was conducted using a questionnaire. Data analysis used multiple linear regression, t-test, UH-f test, and coefficient of determination test. The results showed that all statements regarding employer branding, corporate reputation, organizational attractiveness, and intention to apply were valid with a p-value 0.05. The results of the F test showed that this regression had a calculated F value of 44.160 with a significance value of 0.000